AgriPreneurship and Digital Accounting: Redefining Business Models for Sustainable Agriculture - Nur Muhamad Safii (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
Digital transformation in the agricultural sector has opened up new opportunities for agripreneurs to improve business efficiency and competitiveness in the global market. Digital accounting is present as an important instrument, not only in recording transactions, but also in building transparency, access to financing, and strengthening sustainable business models. However, the adoption of this technology still faces challenges in the form of low digital literacy, implementation costs, and human resource resistance. This study aims to map the driving factors and obstacles to the adoption of digital accounting in agricultural SMEs, examine the role of the integration of Farm Financial Accounts (FFA) and Farm Management Information Systems (FMIS), and formulate a framework for redefining agripreneurship business models towards sustainability. The research uses a qualitative approach with exploratory case studies on agricultural SMEs in West Java. Data were collected through semi-structured interviews, questionnaires, field observations, and digital financial statement documentation, then analyzed by thematic analysis and triangulation techniques. The findings show that the use of digital accounting increases the speed of financial reporting, strengthens credibility in the eyes of financial institutions, and facilitates the integration of Environmental, Social, and Governance (ESG) indicators in business practices. The adoption of digital accounting has also been proven to expand access to financing through banks and fintech, as well as encourage data-driven business model innovation. This research confirms that digital accounting is a strategic catalyst in redefining sustainable agripreneurship business models. The results of the research can be a reference for business actors, technology providers, and policymakers to strengthen digital literacy, provide technology incentives, and integrate ESG principles in agricultural policies.